Kandungan Bahan Kering, Serat Kasar dan Protein Kasar pada Daun Lamtoro (Leucaena glauca) yang Difermentasi dengan Probiotik sebagai Bahan Pakan Ikan [The Content Of Dry Matter, Crude Fiber and Protein from Fermentation Of Leucaena glauca Leaf Using Probiotic As Fish Feed Material] - Agustono Agustono; Devy Rahmawati Putri; Sri Subekti (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract Feed is the element that really support the activities of aquaculture, there for the feed that is available must be adequate and meet the needs of the fish. Efforts to reduce feed costs, some farmers use alternative feed ingredients as a substitute for feed ingredients. Lamtoro leaves in the form of a mixture of flour can be used as fish feed in pellet form. This research been used method with used Completely Randomized Design (CRD) with five treatments and four replications. The treatments used were control (P0), the provision of Probiotics 2% (P1), giving Probiotic 4% (P2), Probiotics administration 6% (P3) and the provision of Probiotics 8% (P4) with each repeated 4 times. Parameters observed were protein content of crude fiber and crude after fermentation for 7 days. These results indicate that administration of probiotics 8% gave significant effect toward crude fiber content in the leaves are fermented and lamtoro which been given Probiotics 6% gave a highly significant effect of the increase in crude protein content in the fermented leaves lamtoro.